The occurrence of polyenoic very long chain fatty acids with greater than 32 carbon atoms in molecular species of phosphatidylcholine in normal and peroxisome-deficient (Zellweger's syndrome) brain. - Poulos, A (1988)
The n-6 tetra- and pentaenoic fatty acids with carbon chain lengths greater than 32 found in normal brain are located predominantly in a separable species of phosphatidylcholine. A similar phospholipid is found in increased amounts in the brain of peroxisome-deficient (Zellweger's syndrome) patients, but the fatty acid composition differs in that penta- and hexaenoic derivatives predominate. Our data strongly suggest that the polyenoic very long chain fatty acids are confined to the sn-1 position of the glycerol moiety, while the sn-2 position is enriched in saturated, monounsaturated and polyunsaturated fatty acids with less than 24 carbon atoms. It is postulated that these unusual molecular species of phosphatidylcholine may play some, as yet undefined, role in brain physiology.